Photothermal ablation of murine melanomas by Fe3O4 nanoparticle clusters - Wang, Xue; Xuan, Lili; Pan, Ying (Beilstein Journal of Nanotechnology, 2022)
Melanoma is one of the deadliest forms of cancer, for which therapeutic regimens are usually limited by the development of resistance. Here, we fabricated Fe3O4 nanoparticle clusters (NPCs), which have drawn widespread attention, and investigated their role in the treatment of melanoma by photothermal therapy (PTT). Scanning electron microscopy imaging shows that our synthesized NPCs are spherical with an average diameter of 329.2 nm. They are highly absorptive at the near-infrared wavelength of 808 nm and efficient at locally converting light into heat. In vitro experiments using light-field microscopy and cell viability assay showed that Fe3O4 NPCs, in conjunction with near-infrared irradiation, effectively ablated A375 melanoma cells by inducing overt apoptosis. Consistently, in vivo studies using BALB/c mice found that intratumoral administration of Fe3O4 NPCs and concomitant in situ exposure to near-infrared light significantly inhibited the growth of implanted tumor xenografts. Finally, we revealed, by experimental approaches including semi-quantitative PCR, western blot and immunohistochemistry, the heat shock protein HSP70 to be upregulated in response to PTT, suggesting this chaperone protein could be a plausible underlying mechanism for the observed therapeutic outcome. Altogether, our results highlight the promise of Fe3O4 NPCs as a new PTT option to treat melanoma.
Keywords: Fe3O4 nanoparticle clusters; heat shock protein 70; melanoma; near infrared; photothermal therapy

(untitled) - Leonardi, G. C.; Falzone, L.; Salemi, R.; Zanghi, A.; Spandidos, D. A.; Mccubrey, J. A.; Candido, S.; Libra, M. (Int. J. Oncol., 2018)

(untitled) - Domingues, B.; Lopes, J. M.; Soares, P.; Populo, H. (ImmunoTargets Ther., 2018)

(untitled) - Hirsch, L. R.; Stafford, R. J.; Bankson, J. A.; Sershen, S. R.; Rivera, B.; Price, R. E.; Hazle, J. D.; Halas, N. J.; West, J. L. (Proc. Natl. Acad. Sci. U. S. A., 2003)

(untitled) - Huang, X.; Jain, P. K.; El-Sayed, I. H.; El-Sayed, M. A. (Lasers Med. Sci., 2008)

(untitled) - O'Neal, D. P.; Hirsch, L. R.; Halas, N. J.; Payne, J. D.; West, J. L. (Cancer Lett., 2004)

(untitled) - Bobo, D.; Robinson, K. J.; Islam, J.; Thurecht, K. J.; Corrie, S. R. (Pharm. Res., 2016)

(untitled) - Yuan, G.; Yuan, Y.; Xu, K.; Luo, Q. (Int. J. Mol. Sci., 2014)

(untitled) - Kievit, F. M.; Zhang, M. (Acc. Chem. Res., 2011)

(untitled) - Laurent, S.; Forge, D.; Port, M.; Roch, A.; Robic, C.; Vander Elst, L.; Muller, R. N. (Chem. Rev., 2008)

(untitled) - Estelrich, J.; Busquets, M. A. (Molecules, 2018)

(untitled) - Di Corato, R.; Espinosa, A.; Lartigue, L.; Tharaud, M.; Chat, S.; Pellegrino, T.; Ménager, C.; Gazeau, F.; Wilhelm, C. (Biomaterials, 2014)

(untitled) - Koo, C.; Hong, H.; Im, P. W.; Kim, H.; Lee, C.; Jin, X.; Yan, B.; Lee, W.; Im, H.-J.; Paek, S. H.; Piao, Y. (Nano Convergence, 2020)

(untitled) - Yu, T.-J.; Li, P.-H.; Tseng, T.-W.; Chen, Y.-C. (Nanomedicine (London, U. K.), 2011)

(untitled) - Chu, M.; Shao, Y.; Peng, J.; Dai, X.; Li, H.; Wu, Q.; Shi, D. (Biomaterials, 2013)

(untitled) - Wang, X.; Kang, C.; Pan, Y.; Jiang, R. (Int. J. Nanomed., 2019)

(untitled) - Shen, S.; Wang, S.; Zheng, R.; Zhu, X.; Jiang, X.; Fu, D.; Yang, W. (Biomaterials, 2015)

(untitled) - Wang, X.; Li, Z.; Ding, Y.; Wang, K.; Xing, Z.; Sun, X.; Guo, W.; Hong, X.; Zhu, X.; Liu, Y. (Chem. Eng. J., 2020)

(untitled) - Chen, D.; Tang, Q.; Li, X.; Zhou, X.; Zang, J.; Xue, W.-q.; Xiang, J.-y.; Guo, C.-q. (Int. J. Nanomed., 2012)

(untitled) - Jiang, Y.; Zheng, W.; Tran, K.; Kamilar, E.; Bariwal, J.; Ma, H.; Liang, H. (Nat. Commun., 2022)

(untitled) - Sun, J.; Zhou, S.; Hou, P.; Yang, Y.; Weng, J.; Li, X.; Li, M. (J. Biomed. Mater. Res., Part A, 2007)

(untitled) - Vostakolaei, M. A.; Hatami‐Baroogh, L.; Babaei, G.; Molavi, O.; Kordi, S.; Abdolalizadeh, J. (J. Cell. Physiol., 2021)

(untitled) - Sun, S.; Zeng, H.; Robinson, D. B.; Raoux, S.; Rice, P. M.; Wang, S. X.; Li, G. (J. Am. Chem. Soc., 2004)

(untitled) - Liu, Z.; Sneve, M.; Haroldson, T. A.; Smith, J. P.; Drewes, L. R. (J. Biol. Chem., 2016)

(untitled) - Watson, A. S.; Soilleux, E. J. (Cold Spring Harbor Protoc., 2015)